Pro-Life, Pro-Choice : Shared Values in the Abortion Debate - Manninen, Bertha Alvarez, 1977- (Book collections on Project MUSE., 2014)
"Debates the pro-choice versus pro-life stance on abortion. Examines the legal status of the fetus in the recent Personhood Amendments in state legislatures and in Supreme Court decisions, and asks whether Roe v. Wade should have focused on the viability of the fetus or on the bodily integrity of the woman"--